Oncologic Safety of the Submental Flap for Reconstruction in Oral Cavity Malignancies. (23rd August 2013) - Howard, Brittany E.; Nagel, Thomas H.; Donald, Carrlene B.; Hinni, Michael L.; Hayden, Richard E.
Abstract : Objectives: 1) Recognize the submental flap as an excellent option for oral cavity reconstruction. 2) Evaluate the oncologic safety of the submental flap given transposition of potentially involved nodal basins to the reconstruction site. Methods: Retrospective chart review of submental flap reconstructions for oral cavity defects secondary to cancer resections performed at a tertiary referral center between 2001 and 2012. Analysis included tumor location, staging, reconstructive details, postoperative course, and outcomes. Results: Fifty patients were identified having undergone submental flap reconstruction of defects following resection for oral cavity malignancies. No patient had identifiable Level I nodal involvement. Patients' ages ranged from 35 to 88 (mean 70) years old. Subsites involved were mobile tongue (n=11), buccal mucosa (n=12), retromolar trigone (n=9), hard palate (n=5), lip (n=3), superior alveolar ridge (n=3), and inferior alveolar ridge (3). AJCC staging of patients included stage II (n=16, 32%), stage III (n=10, 20%), and stage IVa disease (n = 28, 48%). All patients underwent a level 1A and 1B dissection with removal of the nodal basin and submandibular gland. The prevalence of occult lymph node metastasis involving level 1 was 10.6%. On follow‐up there were no local recurrences associated with submental flap transposition to the oral cavity. Tongue recurrence occurred in 1 patient with multifocal disease discrete from the submental flap reconstruction. There was 100% flap survival. Conclusions: The submental flap provides a rapid and reliable option for oral cavity defect reconstruction. With appropriate management of the level 1 nodal compartment oncologic outcomes are not compromised.